Comparing the low-frequency content of exploration seismic source - receiver combinations using surface waves: a field study in Hussar, Alberta - Wu, Yu-Tai; Stewart, Robert R. (Frontiers in Earth Science, 2024)
The low-frequency content of seismic waves in exploration is of substantial value as it can benefit imaging and inversion by providing deeper penetration, broader-band energy, and wavelet stability. However, characterizing the factors contributing to low frequencies (the seismic source, response of the receiver, and spectral signal-to-noise) and their effects may be complicated. The Hussar, Alberta survey, conducted by the CREWES Project at the University of Calgary and used here, addresses this challenge with a range of sources and receiver types. We further analyze the low-frequency content of the Hussar data using surface waves - because of their significant coherent low-frequency energy. The multichannel analysis of surface waves (MASW) method is used. To improve accuracy, a nonlinear approach is applied to extract dispersion properties, overcoming the limitations of conventional methods at low frequencies. This allows for precise phase velocity measurements across frequencies and assesses the frequency content of different source-receiver type combinations based on surface-wave coherence. The extracted dispersion properties were validated by comparing the dispersion curves estimated using Vs from traveltime tomography and well-logging data. The survey tested 2 kg dynamite in addition to vibroseis sources with low-dwell and linear sweeps. The receivers evaluated included Vectorseis accelerometers, as well as 10 and 4.5 Hz geophones. Our dispersion results indicate that all source-receiver combinations contain considerable surface-wave energy down to about 2 Hz. The inverted 1-D Vs models provide Vs estimates to about 800 m, consistent with results from S-wave tomography and shear logging. Dynamite produced more low-frequency energy in surface waves than vibroseis sources, extending below 1.5 Hz. Low-dwell sweeps showed clearer coherence in surface waves at low frequencies than linear sweeps. Of the receivers tested, the 4.5 Hz geophone showed higher sensitivity to low frequencies than both the Vectorseis accelerometer and the 10 Hz geophone. Although the Vectorseis accelerometer recorded more coherent low-frequency surface waves than the 10 Hz geophone, its signals were affected by some instrument noise. Analyzing surface-wave energy and coherency to assess low-frequency content can complement other types of spectral analysis.